Comparative efficacy of different botanicals and chemical insecticides for controlling rice stem borer (Journal of the Bangladesh Agricultural University, 2016)
An experiment was carried out in the field laboratory, Department of Entomology, Bangladesh Agricultural University to find out the efficacy of different botanicals and chemical insecticides against rice stem borer during the period from July to December 2013. The treatments included Neem oil, Mahogany oil, combination of Neem and Mahogany oil, Bishkatali leaf extract, Lantana leaf extract, combination of Bishkatali and Lantana leaf extract, Convoy 25EC, Biesterthoate 40EC, Biesteren 5G and Diatone 10G. The efficacies of treatments were evaluated based on the percent dead heart and white head resulted by rice stem borer infestation at vegetative and reproductive stages, respectively. The efficacies of treatments were varied significantly against the rice stem borers. Among the selected botanicals, Neem + Mahogany oil followed by Bishkatali leaf extract performed best and Bishkatali + Lantana followed by Lantana leaf extract and leaf extract were least effective to reduce dead heart as well as white head at different counting. Similarly, combination of Neem and Mahogany oil gave the maximum yield among the selected botanicals. Diatone 10G showed the best performance to reduce percent dead and white head among the selected chemical insecticides and gave maximum yield among different chemical insecticides. On the other hand, Convoy 25EC was the least effective to control dead heart and white head infestation with yield. Therefore, Neem + Mahogony oil and Diatone 10G were the best to control rice stem borer and to increase the yield of rice grain.J. Bangladesh Agril. Univ. 13(2): 183-189, December 2015